Diagnostic Accuracy of Combined Sonographic and Mammographic Evaluation in Palpable Breast Masses: A Hospital-Based Study in a Tertiary Care Center in Telangana - Divya Raju Alluri; K. Venkat Ram Reddy; RK Reddy (Asian Journal of Medical Radiological Research, 2020)
Background: Palpable breast masses frequently appear in clinical settings. Early and precise differentiation between benign and malignant lumps is essential for appropriate patient care. Mammography, the gold standard for women over 40, often pairs with ultrasound (sonography) to improve diagnostic accuracy, especially for younger women, dense breasts, or inconclusive mammograms. Limited data exist on the efficacy of combining these modalities in India. This study evaluates the combined use of mammography and ultrasonography in diagnosing palpable breast masses and their impact on patient management. Objectives: The primary objective was to assess the diagnostic accuracy of combined mammography and ultrasonography for palpable breast masses, comparing sensitivity, specificity, and predictive values. Secondary objective include analyzing lesion characteristics, correlating imaging findings with histopathology, and examining the impact on biopsy recommendations and clinical decisions. Subjects and Methods: This observational study, conducted at SVS Medical College & Hospital, Telangana, included 100 women aged 18+ with palpable breast masses from January to December 2018. Participants underwent bilateral mammography and targeted ultrasound. Lesions were categorized using the BI-RADS scoring system. Patients with inconclusive results received ultrasound-guided biopsies, with histopathology as the comparison standard. Sensitivity, specificity, PPV, and NPV were calculated for individual and combined imaging. SPSS version 22.0 was used for statistical analysis (p < 0.05 significance). Results: Combined imaging significantly improved diagnostic accuracy over individual modalities. Mammography alone had 78.5% sensitivity and 85.3% specificity, while ultrasonography showed 85.9% sensitivity and 88.1% specificity. Combined, sensitivity reached 94.2% and specificity 91.8%. Among 100 cases, 65 were benign, 35 malignant (confirmed by histopathology). Mammography was superior for detecting microcalcifications; ultrasound excelled in differentiating cystic from solid lesions. The combined approach reduced unnecessary biopsies by downgrading BI-RADS 4 mammographic lesions deemed benign on ultrasound, enhancing diagnostic concordance with histopathology. Conclusion: Combined sonographic and mammographic evaluation enhances the accuracy of diagnosing palpable breast masses, particularly in distinguishing benign from malignant lesions. Mammography is pivotal for detecting micro calcifications, while ultrasound excels in characterizing mass morphology and vascularity. Integrating both into routine practice optimizes biopsy decisions, early cancer detection, and patient outcomes. A dual-imaging approach is recommended as the standard for evaluating palpable breast masses, especially in tertiary care settings.